A new species of predaceous mite of the genus Neoseiulus Hughes (Acari, Phytoseiidae), with redescriptions of N. magnanalis (Thor) and N. ellesmerei (Chant & Hansell), from Svalbard, High Arctic - Kolodochka, Leonid A.; Gwiazdowicz, Dariusz J. (Zootaxa, 2014)
A new species of phytoseiid mite of the genus Neoseiulus (Acari, Phytoseiidae) found in Svalbard is described and illustrated. Redescriptions, drawings, measurements, and diagnosis of two related species, N. magnanalis (Thor) and N. ellesmerei (Chant & Hansell) are given. A neotype is designated for N. magnanalis.